Conditional expression of a dominant-negative form of Epstein-Barr virus (EBV) nuclear antigen EBNALP inhibits EBV-positive lymphoblastoid cell growth - Harada, Shizuko; Saijo, Masayuki (Archives of Virology, 2020)
Epstein-Barr virus (EBV) is a ubiquitous human herpesvirus that transforms primary B lymphocytes, yielding lymphoblastoid cell lines (LCLs). EBV-encoded nuclear antigen 2 (EBNA2) and EBV-encoded nuclear antigen leader protein (EBNALP) are the first viral products expressed after EBV infection of primary B lymphocytes and are essential for EBV-induced B-lymphocyte growth transformation. EBNA2 functions as a transcriptional activator of viral and cellular genes, with EBNALP as a coactivator for EBNA2-mediated transcriptional activation. We previously reported that mutant EBNALP with a C-terminal 10-amino-acid truncation loses the ability to coactivate, and has a dominant-negative effect on wild-type-EBNALP-mediated coactivation. However, the functional relevance of EBNALP in maintenance of LCL cell growth has not been investigated. To address this, we have constructed LCL-derived cell clones in which this dominant-negative form of EBNALP (DNLP) is conditionally expressed by the Cre-loxP system. We used these cells to evaluate the effect of DNLP expression on EBV-induced cell proliferation. After drug treatment, the DNLP-expressing LCL clones showed reduced cell proliferation and viability. These results indicate that EBNALP is critical for maintaining LCL growth and EBV-induced cell proliferation.